Multilingualism among the elderly Chinese in Singapore : an oral account - Nah, Vanessa Ellen Mei Yin (2021)
This study aims to qualitatively document the histories of Singapore's Chinese multilingual elderly. Semi-structured interviews were conducted with seven Chinese Singaporeans aged 75 years and above on how and why they acquired the languages they speak and their attitudes towards these linguistic varieties, of which many are declining in usage. Five participants were multilingual and spoke three or more languages fluently; two spoke only two languages and were included for a balanced and holistic perspective. Common themes from the interviews were identified and discussed. One key finding was that communicative necessity and practicality naturally fuelled language learning. Outside of the home, multilingual individuals acquired varieties from conversing with friends, relatives and customers, or as an educational requirement. Language was tied to ethnic belonging, but, generally, pride to speak a linguistic variety was linked to its functional value, not its associated ethnic identity. Unhappiness was expressed at the waning of the Chinese vernaculars and Baba Malay in Singapore today. Such language loss was seen as a sombre, but unavoidable consequence of Singapore's globalisation and modernisation.